ANALISIS PENGGUNAAN LIMBAH PLASTIK TERTOLAK TERHADAP PERMEABILITAS PAVING BLOCK - -, Nurmila; Puspitasari, Ira (Jurnal Mahasiswa Terapan; Vol 1 No 4 (2025): Jurnal Mahasiswa Terapan, 2025)
This research aims to develop paving blocks by utilizing multilayer plastic waste as a substitution material, treatment through a curing process for 14 days. The method used is an experimental method, focusing on testing the permeability of paving blocks with various variations in plastic waste content. Variations in the composition of rejected plastic waste include: 0% (without plastic), 0.3%, 0.4%, and 0.5%. The results of the average permeability test showed that the sample without plastic waste (0%) had a permeability value of 27.978%, the sample with 0.3% plastic reached 33.632%, the sample with 0.4% plastic was 33.874%, and the sample with 0.5% plastic decreased to 29.084%. Based on these results, the addition of multilayer plastic waste can increase the permeability of paving blocks up to a composition of 0.4%, but higher additions indicate a decrease in permeability. This shows the potential use of multilayer plastic waste in paving blocks with certain composition limitations to achieve optimal permeability.